2014
DOI: 10.1016/j.cell.2014.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of RNA Modification: m6A and U-Tail

Abstract: Although more than 100 types of RNA modification have been described thus far, most of them were thought to be rare in mRNAs and in regulatory noncoding RNAs. Recent developments have unveiled that at least some of the modifications are considerably abundant and widely conserved. This Minireview summarizes the molecular machineries and biological functions of methylation (N6-methyladenosine, m(6)A) and uridylation (U-tail).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
224
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(228 citation statements)
references
References 64 publications
3
224
0
1
Order By: Relevance
“…An argument against this is based on the type of methyladenosine detected in our analysis. N 6 -Methyladenosine is a methylated purine nucleotide enriched in mRNA and microRNA (50,51). We did detect a light-induced decrease of methyl adenosine, but comparison with standards showed that it was N 1 -methyl adenosine.…”
Section: Illumination Influences Nucleotide Metabolismmentioning
confidence: 98%
“…An argument against this is based on the type of methyladenosine detected in our analysis. N 6 -Methyladenosine is a methylated purine nucleotide enriched in mRNA and microRNA (50,51). We did detect a light-induced decrease of methyl adenosine, but comparison with standards showed that it was N 1 -methyl adenosine.…”
Section: Illumination Influences Nucleotide Metabolismmentioning
confidence: 98%
“…consisting of the proteins methyltransferase-like 3 (METTL3), METTL14, and Wilms tumor 1 associated protein (WTAP), the activity of which is opposed by two m 6 A demethylases, fat mass and obesity-associated protein (FTO) and AlkB homolog 5 (ALKBH5) (27,30). In human cells, thousands of mRNAs are subject to m 6 A modification (28,29), which has been implicated in mRNA splicing, nuclear export, and translation (31) as well as microRNA processing (32).…”
Section: Significancementioning
confidence: 99%
“…The addition of U residues at the 3 ′ end can affect cytoplasmic mRNA decay (Norbury 2013;Scott and Norbury 2013;Lee et al 2014a). Oligo(U) sequences have been found at the ends of mRNA poly(A) tails in S. pombe (Rissland and Norbury 2009;Malecki et al 2013), mammalian cells Lim et al 2014), and Arabidopsis (Sement et al 2013); short C/U tags have been found in Aspergillus (Morozov et al 2010(Morozov et al , 2012.…”
Section: Introductionmentioning
confidence: 99%